From the Perspective of Contemporary Young People Talking about Chinese Square Dancing - Han, Zhiran (Pacific International Journal, 2025)
Square dancing is a widely practiced public group dance activity in China, primarily involving middle-aged and elderly individuals. It serves as a form of physical exercise, social interaction, and cultural expression. However, despite its popularity, square dancing has become a source of social tension, particularly between different generations. Younger individuals often express concerns about noise pollution, space occupation, and aesthetic differences, reflecting broader urbanization challenges and shifting cultural dynamics. This study aims to explore contemporary young people’s attitudes toward square dancing, analyzing the underlying social and psychological factors influencing their perceptions. Using a qualitative research approach, including in-depth interviews and discourse analysis, this study examines how generational differences, media representation, and urban public space dynamics shape youth perspectives. The findings suggest that while some young individuals appreciate the social benefits of square dancing, others perceive it as a disruption to their urban experience. This study contributes to the discourse on intergenerational cultural adaptation, offering insights into how cultural activities mediate social interactions in China’s evolving urban environment.